Analysis of the concept of Digital Teaching Competence: a systematic literature review - Mario Hidalgo (Grupo de Investigación "Nodo Educativo" / Red Universitaria de Tecnología Educativa (RUTE), 2024)
The technological revolution experienced in today's society has led educational organisations to assume the responsibility of training skills and abilities for this new context. Despite the high degree of complexity within technology-mediated ecosystems, the scientific literature seems to agree that the development of teachers' digital competence is identified to be a key variable of success. The definition of digital competence is however not clearly delineated. Moreover, direct and indirect interactions within this technology-mediated teaching and learning process are not clearly identified. The objective of this study is to define the concept of Digital Teaching Competence through a Systematic Literature Review published between 2017 and 2022, using the Scopus and Dialnet databases. A total of 316 references in English and Spanish were identified, of which 32 were selected for the final analysis, following the PRISMA protocol guidelines. The results confirm the existence of a high degree of conceptual fragmentation, as well as the lack of agreement on the terminology to be used. There is a need to reach a consensus on a taxonomy that facilitates, on one hand, the analysis of the elements that make up Digital Teaching Competence, and on the other hand, the improvement of the capacity to analyse specific contextual variables that contribute to enhancing technology-mediated teaching and learning processes.